The Famous Hadith of Umm Ma`bad (May Allah be Pleased with her) “Analytical Study” - Taher , Hanaa (Islamic Sciences Journal, 2023)
ABSTRACT The hadith of Umm Maabad (may Allah be pleased with her) is well-known in the books of the Biography of the Prophet. She described the Holy Prophet, when He passed by her to ask for some water and milk, such a unique description that many human beings cannot express. She described what she had felt and how she had noticed the perfection of His beauty, His appearance and the joy of His visage . The blessing, grace, goodness, and benevolence came to Umm Maabad and her husband when the Prophet (peace be upon Him) came to them, after they were in distress, and famine nearly dying. In this story, there are many miracles, the most prominent of which is the milking of a completely exhausted and skinny sheep, and turning milk from it, which made Abu Maabad when seeing this miracle, declaring his conversion to Islam, and followed the Prophet to Madina El Monawara with his wife Umm Maabad (may Allah be pleased with them). Umm Maabad(may Allah be pleased with her) had lived after the death of the Prophet of Allah - to the succession of Othman bin Affan (may Allah be pleased with him), and the companions appreciated her and knew her merits, may Allah Almighty be pleased with the companions of the Prophet of Allah. In my research, followed the analytical method of this famous Hadith. I have studied this Hadith in an analytical study by documenting the Hadith, explaining the unfamiliars, verifying the narrators of the Hadith, explaining the opinions of the Validating scholars, and then explaining the Hadith. May Allah grant success.